Russia : Development Policy Review - World Bank (Washington, DC, 2013)
The objective of this report is to provide an assessment of the development objectives before the Russian Federation. To that end, this report assesses: 1) development outcomes and prospects, and 2) the extent to which the Government has been able to implement its social and structural reform program. The analysis and recommendations herein draw on knowledge acquired through various World Bank activities in Russia as well as on sources external to the World Bank. The report is organized as follows: Chapter 1 discusses development outcomes and prospects, which provides background for the report. Chapter 2 focuses on improving the investment climate by reducing energy subsidies, imposing a payments discipline, and strengthening corporate governance as part of the enterprise restructuring process. Incentives propounded to encourage the growth of small and medium enterprises would include improving the business environment, reforming tax policy, strengthening the financial sector, reforming infrastructure monopolies, promoting competitiveness, improving labor market flexibility, and promoting rural investments. Chapter 3 identifies key macroeconomic challenges and risks. Chapter 4 examines the framework for enhancing human capabilities and protecting vulnerable groups. Finally, Chapter 5 elaborates the steps to be undertaken to reform public sector management, including improving intergovernmental fiscal relations, public financial management, tax and customs administration, civil service, and the justice system.